Effect of long-term fertilization in maize-wheat cropping system on carbon mineralization in soil - Sarveen Kaur; G. S. Dheri; D. K. Benbi (Carbon Management, 2019)
Quantitative information on mineralization of soil organic carbon (SOC) under different long-term nutrient management practices is essential for better assessment of carbon (C) loss from soil. With an aim to evaluate long-term nutrient management effects on C mineralization kinetics in soils, a laboratory incubation study was conducted with soils collected from different depths (0–15, 15–30, 30–60, and 60–100 cm) of a 46-year old maize-wheat experiment. The treatments in the field involved long-term application of 100% N, 100% NP, 100% NPK, 150% NPK, 100% NPK + FYM (farmyard manure), and an unfertilized control. Long-term application of fertilizers significantly (p < 0.05) influenced organic C concentration and C mineralization kinetics in soil. Integrated application of inorganic fertilizers and organic manure (100% NPK + FYM) resulted in greater SOC accumulation and higher potentially mineralizable C in soil compared to other treatments. The microbial biomass carbon (MBC), basal soil respiration (BSR), carbon mineralization (Cmin), and microbial quotient (qMic) values were significantly higher under integrated application of NPK and FYM in maize-wheat system. The results showed that long-term application of FYM along with inorganic fertilizer enhanced SOC pool compared to solitary application of mineral fertilizers.